PRAGMATIC FEATURES OF LITERARY TEXTS: AN ANALYSIS OF SPEECH ACTS, CONTEXT, AND IMPLICATURE - Zilola Khusniddin qizi Sayitqulova (Bright Mind Publishing, 2025)
Literary texts are not merely aesthetic artifacts but function as complex communicative systems where the author’s intention, the reader’s interpretation, and the pragmatic functions of language units interact. This article investigates the pragmatic features of literary discourse, focusing on the role of speech act theory, context, and implicature in shaping meaning and interaction. Drawing from Uzbek, Russian, and English literature, the study explores how indirect communication mechanisms manifest through linguistic and extralinguistic cues. The paper adopts a comparative, discursive, and linguo-pragmatic approach to analyze hidden meanings, presuppositions, and pragmatic strategies. Findings reveal that cultural and linguistic contexts significantly influence how pragmatic elements operate in literary communication, emphasizing the need for deeper empirical analysis in literary pragmatics.
Keywords: Literary pragmatics, speech acts, implicature, context, literary discourse, cross-cultural analysis, linguistic communication.